Influence of Soil Physicochemical Properties and Inter-Root Microbial Communities on the Inhibition of Anthracnose in Peppers - Yongbin Ma; Miaomiao Liu; Yuting Hong; Yichao Wang; Xiaoke Chang; Gongyao Shi; Huaijuan Xiao; Qiuju Yao; Fan Yang (Microorganisms)
Anthracnose is a widespread plant disease affecting vegetables, flowers, crops, and fruit trees, causing significant economic losses. It occurs at various stages of pepper growth, leading to rotting and shedding in later stages. The aim of this study was to explore the relationship with anthracnose occurrence by analyzing the physicochemical properties and microbiota changes in the inter-root soil of pepper under different susceptibility levels to reveal the key microecological factors and dominant microbial populations and to provide reference for ecological control. Illumina Miseq sequencing was first used to evaluate the physicochemical properties and microbial taxa in pepper inter-root soil across different health statuses and identify key parameters associated with anthracnose. Subsequently, PICRUSt2 (systematic genetic Investigation of communities by Reconstruction of observed States 2) and FUNGuild (Fungi Functional Guild) V1.0 online platform were used to predict the activities of inter-root bacteria and fungi. The findings indicated that healthy peppers had significantly higher inter-root soil nutrient levels and enzyme activity compared to sensitive peppers. There were significant differences between their community structures. In alpha-diversity analysis, inter-root soil microbial richness and diversity were significantly higher in healthy peppers than in susceptible peppers. At the bacterial taxonomic level, the comparative prevalence of Acidobacteria in highly resistant plants, resistant plants, and susceptible plants decreased sequentially. At the genus level, the relative abundance of Vicinamibacteraceae and RB41 was markedly elevated in disease-resistant inter-root soils than in disease-susceptible soils. At the fungal level, the comparative prevalence of Ascomycetes in highly resistant plants, resistant plants, and susceptible plants increased sequentially. Differences in function are mainly manifested in apoptosis and mycelial development.